2023
DOI: 10.3390/rs15041066
|View full text |Cite
|
Sign up to set email alerts
|

Exploring PlanetScope Satellite Capabilities for Soil Salinity Estimation and Mapping in Arid Regions Oases

Abstract: One reason for soil degradation is salinization in inland dryland, which poses a substantial threat to arable land productivity. Remote-sensing technology provides a rapid and accurate assessment for soil salinity monitoring, but there is a lack of high-resolution remote-sensing spatial salinity estimations. The PlanetScope satellite array provides high-precision mapping for land surface monitoring through its 3-m spatial resolution and near-daily revisiting frequency. This study’s use of the PlanetScope satel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 65 publications
0
2
0
Order By: Relevance
“…The study outcomes have revealed the substantial transferability of satellite-based radar and optical environmental variables within an arid region, substantiating their potential for generating beneficial outputs. For transferability of soil salinity levels in arid regions using ML algorithms, the PlanetScope satellite [96] can offer important opportunities to capture the spatial variability of salinity [97].…”
Section: Discussionmentioning
confidence: 99%
“…The study outcomes have revealed the substantial transferability of satellite-based radar and optical environmental variables within an arid region, substantiating their potential for generating beneficial outputs. For transferability of soil salinity levels in arid regions using ML algorithms, the PlanetScope satellite [96] can offer important opportunities to capture the spatial variability of salinity [97].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, soil salinization also affects surface and underground water quality, animal and plant communities, and human health, posing a serious threat to the ecological environment and biosphere [13]. Therefore, rapid acquisition and accurate monitoring of soil surface salinity information have important reference significance for achieving comprehensive utilization and productivity improvement of soil [14].…”
Section: Background and Motivationmentioning
confidence: 99%
“…Prior studies commonly utilized conventional satellite-mounted multispectral sensors or synthetic aperture radar (SAR) to acquire remotely sensed imagery to invert soil salinity ( Wang J. et al., 2019 ). Despite their easy accessibility, these data sources often exhibit drawbacks like low spatial ( Tan et al., 2023 ) and spectral resolution alongside lengthy revisit periods ( Fan et al., 2021 ). While the lower spatial resolution and longer revisit period are advantageous for soil salinity detection across vast regions ( Sahbeni et al., 2023 ), precision agriculture requires a method apt for monitoring soil salinity in smaller areas.…”
Section: Introductionmentioning
confidence: 99%